The Relationship between Job Satisfaction and Organizational Commitment: Case Study of Employees in PT X - Karina Yoveline (iBuss Management, 2015)
Human resource management plays a vital role in a company as it could affect company’s performance. In the last decade, companies are faced with high turnover of Generation Y or Millennial Generation. PT X as a manufacturing company that relies on human capital heavily is in a tight competition with other company. This research is done for the purpose to see whether job satisfaction really has significant correlation with organizational commitment, which may reduce the number of turnover. Data  was  gathered  using  simple  random  sampling  by  distributing questionnaires  to  138  employees  in  PT X.  It  was  then  analyzed  by  using  multiple  linear regression.  The  result  shows  that  the  job satisfaction  simultaneously  has  significant  correlation with  organizational commitment.  Meanwhile,  as  individual  dimensions,  all but fringe benefit has significant correlation with organizational commitment.Keywords: human resource management, job satisfaction, organizational commitment.